Improving students' reading comprehension skills through the survey, question, read, recite, review (SQ3R) method - Samuel Sinulingga; Erikson Saragih; Christin Agustina Purba (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This research describes the development of the ability to understand reading content and student activity when learning using the SQ3R method at XII APT SMK Negeri 1 Panai Hulu T.P 2022/2023. They used two cycles for 16 weeks in Odd Semester. The results of 2 rounds of research obtained the following: 1. Reading Skills Students' comprehension improves by using the SQ3R method. A mean of 65 was obtained during the first ability test, with a final classical percent of 45%. And in the second ability test, a mean result of 85 was obtained with a final class percentage of 87%, and 31% progress was obtained. The result was an increase, and a minimum requirement of the Indonesian language was achieved. 2. There is an increase in students' activities in absorbing teaching materials by applying the SQ3R method.